Regulation of human heterochromatin protein 1 binding protein 3 (HP1BP3, also known as HP1BP74) in response to the DNA damage - Normatova, Makhliyo (2016)
DNA damage can result from exposure to exogenous agents such as ionizing radiation (IR), ultraviolet radiation (UV), environmental toxins and drugs or from endogenous sources such as reactive oxygen species or errors during DNA replication. DNA repair involves both post-translational modification of nucleosomes and concentration of DNA repair proteins at the damaged site(s). Therefore, the nucleosome rearrangement and chromatin disassembly with histones and other non-histone proteins upon damage must be in a dynamic balance with chromatin reestablishment following repair. Any impediment of this regulation process may cause extensive damage and trigger the growth of tumours. However, most studies have mainly focused on the core histones, whereas the heterochromatin proteins and their partners’ identity remained unknown.